INTERPRETATION PRACTICES AS AN INNOVATIVE FORM OF CULTURAL HERITAGE PRESERVATION AND POPULARIZATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article describes the role of such formats of museum activity as interpretation, its methods and its significance for tourist attraction and improving the quality of human capital.